PENGARUH MODEL PEMBELAJARAN MIND MAPPING TERHADAP HASIL BELAJAR MATA PELAJARAN IPAS PADA SISWA KELAS V SDN 101960 GALANG - Three Angel Grace Silitonga; Juliana; Dyan wulan Sari HS; Reflina Sinaga; Ester Julinda Simarmata; Patri Janson Silaban (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of this research is to find out whether there is an influence of using the mind mapping learning model on science learning outcomes in class V SD Negeri 101960 Galang. The population in this study were all class V students at SD Negeri 101960 Galang. Total sampel were 27 people. This research uses an experimental type of research. This experimental method was carried out to determine the results of comparisons between groups that were given treatment and those that were not given treatment. The independent variable in this research is the mind mapping learning model, while the dependent variable is science learning outcomes. The analysis method was carried out descriptively and used the paired t test. The research results showed that the science learning outcomes of students who were taught by applying the mind mapping learning model to the science learning outcomes for class V SD Negeri 101960 Galang obtained an average score of 89. The learning outcomes of students without using the mind mapping obtained an average score of 78. There is a significant influence of the use of the mind mapping learning model on student learning outcomes in class V SD Negeri 101960 Galang.